A new species of Miobantia Giglio-Tos, 1917 with a novel morphological feature (Mantodea: Thespidae: Miobantiinae) - Scherrer, Marcus V.; Agudelo, Antonio A. (Zootaxa, 2019)
Thespidae is the most diverse family among the Neotropical Mantodea, currently containing 33 genera and 146 species of praying mantises (Wieland & Svenson, 2018). Miobantia Giglio-Tos, 1917 are small, dark coloured mantids, often found in low vegetation of humid forests near the South American Atlantic coast, from the Brazilian Northeast to the Argentine Patagonia (Scherrer, 2014). Males are active fliers, while females, apterous, are often found in leaf litter or in plants close to the ground (Scherrer, 2014; Santos et al., 2018). Despite their commonness in the Brazilian Atlantic Forest the genus received little taxonomic attention, yet had a complicated nomenclatural history. Scherrer (2014) provided a comprehensive taxonomic and nomenclatural revision of Miobantia after incorporating both molecular and morphological data to reorganize the group, resulting in the description of four new species, detailed identification keys, illustrations, association of conspecific sexes, and maps for all known species. The most recent contribution to the taxonomy of the genus was the addition of Metathespis precaria Piza, 1968 as a junior synonym of Miobantia rustica (Fabricius, 1781) (Agudelo & Rivera, 2015).